#TITLE_ALTERNATIVE# - GADI (NIM : 12308044), ADNAN
Improved signal to noise ratio is a very important aspect in seismic data processing. One of the processes to improve the s/n ratio is deconvolution. In conventional deconvolution, it is assumed that the existing wavelet is stationary, which means physically invariant pulses that appear on each reflector is incidental, or it could also be said that the wavelet does not change the travel time. We conducted Gabor deconvolution which think that the Earth's wavelet is nonstationary. By using this method, the time-variant filter earth contained in seismic recordings can be captured and eliminated. Gabor deconvolution is done by performing calculations in the frequency domain. Gabor transformation results from seismic traces then divided by the estimated attenuation and source wavelet. After we got the results, we conducted Gabor inverse transformation to return the existing spectrum in the time domain.